A long-wavelength ultrasensitive colorimetric fluorescent probe for carbon monoxide detection in living cells. Issue 7 (19th June 2019) - Wang, Zuokai; Zhao, Ziyang; Liu, Caiyun; Geng, Zhuofan; Duan, Qingxia; Jia, Pan; Li, Zilu; Zhu, Hanchuang; Zhu, Baocun; Sheng, Wenlong
Abstract : A long-wavelength ultrasensitive colorimetric fluorescent probe was developed to track carbon monoxide in living cells. Abstract : Exploring techniques for monitoring the intracellular signaling molecule carbon monoxide (CO) in biosystems is important to help understand its various cellular functions. Therefore, a simple long-wavelength colorimetric fluorescent probeLW-CO was designed for selectively and sensitively detecting intracellular CO in living systems. ProbeLW-CO is ultrasensitive and can track CO levels in the range of 0–1 μM, with a detection limit of about 3.2 nM. Additionally, the obvious color changes of probeLW-CO with CO (yellow to pink) provide a convenient way for on-site detection of CO with the naked eye. ProbeLW-CO was applied to track the exogenous levels of CO in RAW264.7 cells. ProbeLW-CO proved to be an efficient method for investigating various cellular functions of CO.